Cherubs holding lamp post - Ghosh, Ayan (2023)
Three winged cherubs hold up a stump over the central pediment of the triple-arched gateway. The stump originally held a gas-powered lamp. Three gas lamps were placed on top of the triple-arched gateway, one over each arch, but were later removed.